Platelet Disorders and Medication Strategies - Zhang, Zhao; Zhou, Xianghui; Fang, Xiyuan; Zhou, Xin; Cheng, Zhipeng; Hu, Yu (Thrombosis and Haemostasis, 2025)
Platelets are among the most abundant cells in the body and play important roles in coagulation and immunity. Platelets are formed when hematopoietic stem cells proliferate and differentiate into megakaryocytes via the regulation of various cytokines. After the megakaryocytes mature in the bone marrow cavity, proplatelets are released into the blood circulation where they eventually remodel into mature platelets. Given that the production and functions of platelets involve the regulation of many factors—such as hematopoietic stem cells, the hematopoietic microenvironment, and cytokines—the causes and mechanisms of platelet-related diseases are diverse, often involving platelet production, clearance, and distribution. In this review, we examined the regulation of platelet production and summarized common disorders affecting platelet quantity, namely, thrombocytopenia and thrombocytosis. In addition, we reviewed previous clinical studies and summarized the medication strategies commonly used for the treatment of different platelet disorders in different clinical scenarios.
Keywords: platelets; thrombocytopenia; thrombocytosis; medication